Analysis of the experience of the geriatric fracture program in two institutions in Colombia: a reproducible model? (Colombia Medica, 2021)
Background: hip fracture is the major cause of morbidity and mortality. Geriatric fracture programs promise to improve the quality of care, health outcomes and reduce costs.Objective: To describe the results related to the Geriatric fracture programs implementation in two Colombian institutions. These results could then be compared to other published experiences to assess reproducibility of the program.Methods: A retrospective descriptive study of the patients treated under the Geriatric fracture programs in two institutions in Colombia was carried out. The information of each institution was collected from the initial year of program implementation until 2018. Demographic characteristics, length of stay, hospitalization complications, readmissions and mortality were described. Consumption of healthcare resources was defined using base cases determined with local experts and costs were estimated using standard methods.Results: 475 patients were included in the Geriatric fracture programs in two institutions. We observed an increase in the number of patients during the Geriatric fracture programs. The length of stay decreased between 8.5% and 26.1%  as did the proportion of total complications, with delirium having the greatest reduction. A similar situation was seen for first year mortality (from 10.9% to 4.7% in one institution and form 11.4% to 5.1% in the other), in-hospital deaths and readmissions. Estimates of costs of stay and complications showed reductions in all scenarios, varying between 22% and 68.3% depending on the sensitivity scenario.Conclusions: The present study presents the experience of two institutions that implemented the Geriatric fracture programs with increase in the number of patients treated and reductions in the time of hospital stay, the proportion of complications, readmissions, mortality, and estimated costs. These are similar between both institutions and with other published implementations. This could hint that geriatric fracture program may be implemented with reproducible results.